Dampak Keterkaitan Emosional dan Informasi Influencer dalam Mendorong WOM dan Niat Pembelian Produk Short Course - Angin, Pettia Weharima Perangin; Andriani, Meta (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
This study investigates the influence of emotional attachment and perceived information value of an influencer on the intention to purchase short course products. Drawing upon Social Influence Theory and the Theory of Reasoned Action, this research also examines perceived influence as a mediating variable. Data were collected through an online survey targeting followers of Ferry Irwandi, an educational and social issue-focused influencer. A total of 95 valid responses were analyzed using Structural Equation Modeling with the PLS-SEM approach. The results reveal that emotional attachment and behavioral loyalty significantly affect perceived influence, while perceived information value does not show a significant impact. Furthermore, perceived influence positively influences both word-of-mouth (WOM) behavior and purchase intention. Mediation analysis shows that emotional attachment indirectly affects purchase intention through perceived influence and WOM, whereas behavioral loyalty and perceived information value do not have a significant indirect effect. These findings suggest that emotional connection with an influencer plays a critical role in shaping followers’ perception and behavioral responses toward digital educational products. The study highlights the strategic importance of building strong emotional ties and perceived credibility in influencer marketing, particularly for promoting non-formal learning services. Marketers and digital learning providers are advised to prioritize influencers who resonate with their audience’s values to enhance recommendation behaviors and increase conversion intentions.